The Reference of Grammatical Cohesion in the Recess Therapy Youtube Channel - Nehe, Imeldayanti; Ambalegin, Ambalegin (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The objective of this research was to identify distinct types of reference grammatical cohesion generated by children between the ages of two and nine in New York City based on the theory of Halliday & Hasan (1976). The data source of this research was the Recess Therapy YouTube channel. This research applied the qualitative research method defined by Creswell (2013). This research used an observational method to collect the data. In analyzing data, the researchers applied the identification method and identity technique. The result of this research the researchers found 364 data that were categorized into three types. There were 180 data that indicated personal references. Next, there were 97 data categorized as demonstrative references and the last, there were 87 data indicated comparative references. Grammatical cohesion is critical in this process because it provides the language processes required to link, organize, and express meaning within written speech. Recognizing the significance of grammatical cohesiveness is critical for those who want to improve their communication abilities since it allows them to produce coherent structures, and effective.